Portrayals of the â€œCommonâ€ Poor as [Un]common Wealth in the Sri Lankan Novel of Expatriation - Perera, Senath Walter (SARE: Southeast Asian Review of English, 2017)
In her paper, â€œ Can the Indigent Speak? Poverty Studies, the Postcolonial and Global Appeal of Q &A and The White Tiger,â€ Barbara Korte responds in the negative to her rhetorical question, â€œare the non-poor disentitled to write about poverty?â€ before proceeding to critique some novelistic renderings of the indigent by writers who are obviously not impoverished (294). One could ask a similar question in relation to Sri Lanka and frame it thus: â€œAre Sri Lankan expatriate writers, who are separated from the land of their birth by time and space, entitled to write about the poor in the island, especially domesticsâ€? To this, and the possible follow up question, â€œDosome of these depictions of the poor and their interrelations with the moneyed class challenge the postcolonial critic?â€one could respond with an emphatic â€œyes.â€